The roles of culture, gender norms, and sexual orientation in intimate partner violence: Psychosocial variables associated with IPV in a Portuguese sample - Cañete, M. (2023)
Intimate partner violence (IPV) has been recognized as a threat to the well-being of women and men in different-sex and same-sex relationships worldwide. Research on this topic has been increasing, but more information on the variables associated with IPV may improve responses to IPV prevention and intervention. With this study, we aim to analyze the relationship between psychosocial variables and frequency of IPV, in potential male and female victims in different-sex and same-sex relationships. Three hundred four participants (232 women—76.3%; 72 men—23.7%) were recruited via an online survey, and inquired on sociodemographic data, suffered violence using the Conflict Tactics Scale-2 (CTS-2), and psychosocial variables (e.g., familiar isolation, self-esteem, selfblame, dependence). Overall, higher frequency of violence was associated with higher family and social isolation for both female and male participants. For female participants, a model that considers both sociodemographic variables and psychosocial ones (e.g., social isolation, submission, dependence) best predicted frequency of experienced violence (R2 = 33.1%). For males, only three psychosocial variables predicted experienced violence (e.g., social and familiar isolation, and submission), and retained more explicative power (R2 = 41.3%). No significant differences were found in the victimization between victims in different-sex and same-sex relationships, but family isolation was higher in same-sex relationships. Our findings shed light on relevant variables and their potential contribution to explain the frequency of violence among male and female participants, in different and same-sex relationships. Future prevention and treatment interventions could be improved by taking into consideration the relevance of these variables.